Sumpah Allah dengan Makhluk-Nya Dalam Q.S. al-‘Asr - Fauzi Fathur Rozi; Qonitah Hafidzah; Shohebul Hajad (STAI Al-Mujtama Pamekasan, 2023)
The Qur'an is the word of Allah which has the value of miracles, which was revealed to the Prophets and Messengers, through the angel Gabriel. It serves as a guide for humans and as a differentiator between truth and falsehood. In the Qur'an there are many mentions of oaths (Qasam) which can be interpreted as expressions used to give affirmation. There are three elements in it, namely Fi'il Qasam, Muqsam Bih, and Muqsam 'Alaih. The fall of Q.S. al-‘Asr” Allah shows that there is no unlucky or lucky time, all times are the same. What is influential is the goodness and badness of one's business. Time is always neutral. Time cannot be cursed, nor can it be called unlucky or lucky. Time (time) is one of His creatures in which various events, evil and good occur. the function of time revealed by the Qur'an (1) Tool or media in determining worship. (2) Media Introspection. (3) Future plans. Some things about Allah's oath by using time are (1) Time contains various miracles, (2) One of the great points of favor, (3) Time flies quickly, and (4) Time will not return. Allah swears by the period (time) as mentioned in QS. al-Asr, because it contains various miracles. Allah takes time (time) as an oath, reminding us that, living in this world through time and when the time has passed, the time that we can use cannot be repeated.",